The organizational identity of Ukrainian universities as claimed through their mission statements. Issue 4 (1st October 2016) - Hladchenko, Myroslava
Abstract : After the Revolution of Dignity (2014), Ukraine signed an Association Agreement with the European Union. In the context of European integration, new legislation on higher education has been adopted. Changes in the institutional environment expect responses from higher education institutions, in particular changes in the organizational identities of Ukrainian universities that are claimed through the mission statements. As Ukrainian universities are in the stage of transition from the Soviet past to the European future, it is of primary importance how they interpret and respond to the changes in the institutional environment, claiming their organizational identity through mission statements. To answer this question, sociological institutionalism is applied as a theoretical framework for the exploration of how institutions shape the organizational identities of universities. A content analysis of the mission statements of 46 Ukrainian universities was conducted: 26 defined before the adoption of the new legislation on higher education in 2014 and 20 formulated after this date.